Gut microbiota dysbiosis in rats with LPS-induced liver diseases affected by Aronia melanocarpa polyphenols - Kong, Yanwen; Li , Dongnan; Meng, Xianjun (Food Science and Technology, 2023)
It is well known that there is an imbalance of gut microbiota in liver diseases, our previous study has proved that Aronia melanocarpa polyphenols (AMPs) can modulate the gut microbiota and affect the progression of liver diseases. Here, we analyzed the gut microbiota by 16S rRNA sequencing and bioinformatic analysis to explored the changes of gut microbiota composition and functions after LPS and AMPs intervention. Our results showed that there were significant differences in the gut microbiota structure between different treatment groups, such as increasing the abundance of Lactobacillaceae and Muribaculaceae, decreasing the abundance of Ruminococcaceae and Acidaminococcaceae. Furthermore, PICRUSt prediction showed that 29 functional pathways have changed significantly which may promote the treatment of liver diseases. This study could help to supplement the information about the community of gut microbiota in liver diseases and provide a new strategy for the treatment of liver diseases.